Cartas de crédito como medio de pago que genera confianza en el mundo de los negocios internacionales - Pico, Lucía (2018)
The present investigation responds to a descriptive study, whose objective is to know the security and confidence that letters of credit provide in commercial transactions. To achieve the aforementioned objective begins with the premise from knowing what is a letter of credit? And the benefits that can be obtained by the parties involved. Ecuador has financial entities in charge of advising and issuing letters of credit to companies that carry out international trade and that require it as a means of reliability to guarantee commercial operations, however this in turn has characteristics and rules that regulate and control their use within of international parameters. The present study concludes with the description of the benefits obtained by the parties involved despite the costs that affect the use of this document